Molecular and rheological characterization of different cell wall fractions of Porphyridium cruentum. (1st September 2018) - Bernaerts, Tom M.M.; Kyomugasho, Clare; Van Looveren, Noor; Gheysen, Lore; Foubert, Imogen; Hendrickx, Marc E.; Van Loey, Ann M.
Highlights: Extracellular polysaccharides (EPS) consist of high molecular weight polymers. EPS show a higher intrinsic viscosity than several currently used thickening agents. Cell wall polysaccharides have same sugar profile as EPS, but lower molecular weight. None of the polysaccharide solutions gel by cold-set or heat-set gelation. EPS show large potential as a new sustainable thickening agent. Abstract: Cell wall related polysaccharides of the red microalga Porphyridium sp. were shown to be a promising source of new sustainable thickening agents. Isolated extracellular polysaccharides (EPS) consisted of high molecular weight polymers, showing a higher intrinsic viscosity compared to several commercially used hydrocolloids. Aqueous solutions of EPS (2% w/w) were characterized by substantial viscosities and weak gel behavior. Even though the extracted water soluble cell wall polysaccharides exhibited the same monosaccharide profile as EPS (composed of galactose, glucose, xylose and glucuronic acid), a lower molecular weight and intrinsic viscosity was observed for this fraction, resulting in poor rheological properties. Therefore, it was hypothesized that the physicochemical properties were related with a different molecular structural organization of these monosaccharides and sulfate groups. The main challenge for commercialization of extracellular polysaccharides of Porphyridium sp. remains the purification of these fractions to obtain polysaccharide extracts with low protein and salt contents.